Gaining Customer Experience Insights That Matter. (February 2019) - McColl-Kennedy, Janet R.; Zaki, Mohamed; Lemon, Katherine N.; Urmetzer, Florian; Neely, Andy
Contextualized in postpurchase consumption in business-to-business settings, the authors contribute to customer experience (CX) management theory and practice in three important ways. First, by offering a novel CX conceptual framework that integrates prior CX research to better understand, manage, and improve CXs—comprised of value creation elements (resources, activities, context, interactions, and customer role), cognitive responses, and discrete emotions at touchpoints across the customer journey. Second, by demonstrating the usefulness of a longitudinal CX analytic based on the conceptual framework that combines quantitative and qualitative measures. Third, by providing a step-by-step guide for implementing the text mining approach in practice, thereby showing that CX analytics that apply big data techniques to the CX can offer significant insights that matter. The authors highlight six key insights practitioners need in order to manage their customers' journey, through (1) taking a customer perspective, (2) identifying root causes, (3) uncovering at-risk segments, (4) capturing customers' emotional and cognitive responses, (5) spotting and preventing decreasing sales, and (6) prioritizing actions to improve CX. The article concludes with directions for future research.